Human medial temporal lobe damage can disrupt the perception of single objects. - Lee, A; Rudebeck, SR (2010)
The idea that the medial temporal lobe (MTL), traditionally viewed as an exclusive memory system, may also subserve higher-order perception has been debated fiercely. To support this suggestion, monkey and human lesion studies have demonstrated that perirhinal cortex damage impairs complex object discrimination. The interpretation of these findings has, however, been disputed because these impairments may reflect a primary deficit in MTL-mediated working memory processes or, in the case of human patients, undetected damage to visual processing regions beyond the MTL. To address these issues, this study investigated object perception in two human amnesic patients who were chosen on the basis of their lesion locations and suitability for detailed neuroimaging investigation. A neuropsychological task with minimal working memory demands was administered in which participants assessed the structural coherency of single novel objects. Critically, only the patient with perirhinal atrophy was impaired. Moreover, volumetric and functional neuroimaging data demonstrated that this deficit cannot be attributed to the dysfunction of visual cortical areas. Additional analyses of eye-movement patterns during the perceptual task revealed an inability of this patient to detect structural incoherency consistently. This study uses a combination of techniques to provide strong evidence that the perirhinal cortex subserves perception and suggests that the MTL perceptual-mnemonic debate cannot be dismissed on the basis of anatomy or a working memory impairment.